Studies on Some Anionic Complexes of Co(II), Ni(II) and Cu(II) - Naik, S.; Purohit, K.M.; Patel, R.N. (Asian Journal of Chemistry, 2010)
A series of complexes of the type [LH2] [MCl4L´2] where L = o-phenylene diamine (o-PDn) or diethylene diamine (Den); M = Co(II), Ni(II) and Cu(II); L´-pyridine, γ-picoline and quinoline have been isolated in non-aqueous medium. The compounds were characterised on the basis of their elemental analyses, molecular weight, conductivity, magnetic moment, infrared and electronic spectral data.